Conocimientos y actitudes sobre la detección temprana del cáncer de próstata Ciudad De Dios - Bazán De La Cruz, Shirley Tatiana (2016)
Research study quantitative, descriptive, basic, correlational type and crosssectional, which was conducted in order to determine the relationship between the level of knowledge and level of attitudes for early detection of prostate cancer of residents of the town center City of God. The sample was selected through a simple random probability sampling, the result was 114 people over 45 years. It was used as a tool for data collection a questionnaire and a Likert -type scale, which was built based on other instruments of similar studies. Data processing was performed using the Microsoft Excel program office, statistical charts that allowed a clear understanding of the results was made. In the statistical analysis Chi square test was used; concluding: 64.0 % of people have low knowledge level, 70.2 % of people have attitudes of indifference, 1.8% of people with high level of knowledge have indifference at the level of attitudes; there is no significant relationship knowledge level with the level of attitudes.